Comparison of intravenous ceftriaxone and ciprofloxacin in prevention of infection in cirrhosis patients with variceal bleeding - Chaudhary, Ram Dev; Jamil, Ommar; Kunwar, Sandeep Raj; Ayub, M.; Sarwar, Shahid; Cheema, Tahira Murtaza (International Journal of Advances in Medicine, 2023)
Background: Patients with variceal gastrointestinal bleeding are very susceptible to bacterial infections. This study was designed to examine the effectiveness of ciprofloxacin and ceftriaxone in controlling in-hospital morbidity, mortality, and infection in variceal bleeding patients. Methods: From August 2010 to August 2012, an interventional randomized controlled clinical trial was conducted in the Department of Gastroenterology, East Medical Ward, Mayo Hospital, Lahore. Adult patients who were diagnosed to have gastroesophageal variceal bleeding after endoscopic examination were included. These patients were randomly distributed to 2 groups. Group ceftriaxone: receiving injection Ceftriaxone 1000 mg intravenously 12 hourly for 7 days, Group ciprofloxacin: receiving injection ciprofloxacin 200 mg intravenously 12 hourly for 7 days. Results: Most common viral etiology was Hepatitis C in both the study groups. It was observed that in the ceftriaxone group, 4.8% had rebleeding, while in the ciprofloxacin group 5.6% had rebleeding (p=0.77), one case each had porto-systemic encephalopathy (p=0.99), 0.8% in ceftriaxone group and 3.2% in ciprofloxacin group had spontaneous bacterial peritonitis (p=0.39) and 4.8% in ceftriaxone group and 8% in ciprofloxacin group had systemic inflammatory response syndrome (p=0.31). No patients died during one week follow up. Conclusions: From our study, it was concluded that ciprofloxacin and ceftriaxone had same efficacy when used intravenously for prevention of bacterial infection and improvement in mortality and morbidity in patient of variceal bleeding. Future multicentric studies are required with a longer patient follow to support our findings.